Virtuous emotions - Kristjánsson, Kristján 1959- (Oxford, United Kingdom Oxford University Press, 2018)
"Many people are drawn towards virtue ethics because of the central place it gives to emotions in the good life. Yet it may seem odd to evaluate emotions as virtuous or non-virtuous, for how can we be held responsible for those powerful feelings that simply engulf us? And how can education help us to manage our emotional lives? The aim of this book is to offer readers a new Aristotelian analysis and moral justification of a number of emotions that Aristotle did not mention (awe, grief, and jealousy), or relegated, at best, to the level of the semi-virtuous (shame), or made disparaging remarks about (gratitude), or rejected explicitly (pity, understood as pain at another person's deserved bad fortune). Kristján Kristjánsson argues that there are good Aristotelian reasons for understanding those emotions either as virtuous or as indirectly conducive to virtue. 'Virtuous Emotions' begins with an overview of Aristotle's ideas on the nature of emotions and of emotional value, and concludes with an account of Aristotelian emotion education." --Provided by publisher.
Introduction: developing an Aristotelian account of virtuous emotions -- Emotions and moral value -- Gratitude -- Pity -- Shame -- Jealousy -- Grief -- Awe -- Educating emotions -- Conclusions and afterthoughts.
Includes bibliographical references (pages [203]-219) and index.
Keywords: Aristotle -- Knowledge -- Emotions; Emotions -- Moral and ethical aspects; Emotions (Philosophy); Virtues